PERANCANGAN PERANGKAT LUNAK ENKRIPSI SMS MENGGUNAKAN ALGORITMA RC6 DAN RIJNDAEL PADA SMARTPHONE - Syarifudin, Gusti; Kristianto, Benny Djoede; Gat, Gat (STMIK PONTIANAK, 2020)
Sending text messages is done on a smartphone device is basically the text message delivery without doing a safeguard against the content of the messages sent, so that when it is done tapping against the Groove pengirimanya then intercepted text messages can be directly read by the tappers. For that it needs the software as a specific encoding method support so that the message sent is secure. This research uses the form of research studies, literature research method using Research & Development (R & D). As for the technique of data collection using the study documentation and observation to acquire the theory and algorithm rijndael rc6 algorithm. While the method of software design using Rapid Application Development (RAD). The design of software using the java programming language. The results of this design generates a software named